Evaluation Of Financial Performance Effectiveness Through the Risk-Based Capital (RBC) Ratio Approach AT PT Asuransi Maximus Graha Persada Tbk Listed on The Indonesia Stock Exchange - Windi Astuti; Fauziah Kumalasari (Program Studi Akuntansi Universitas Simalungun, 2026)
This study aims to analyze the effectiveness of the financial performance of PT Asuransi Maximus Graha Persada Tbk during the 2020–2023 period based on liquidity and solvency indicators. The research employs a quantitative approach using secondary data obtained from the company’s annual financial statements. The analysis was conducted through the calculation of financial ratios, including the current ratio, cash ratio, debt to assets ratio, debt to equity ratio, and the Risk Based Capital (RBC) ratio as a key indicator of health for insurance companies. The results show that the company’s liquidity level is categorized as very strong, with an average current ratio of 202.75% and an average cash ratio of 70.5%, both exceeding the respective industry standards of 200% and 50%. Conversely, the company’s solvency level is classified as less healthy, indicated by an average debt to assets ratio of 58% and an average debt to equity ratio of 141.25%, each surpassing the industry thresholds of 40% and 70%. Meanwhile, the company’s RBC value averages 180.5% during the study period, signifying a very healthy financial condition as it is well above the minimum requirement set by the Financial Services Authority (OJK) of 120%. These findings indicate that while the company demonstrates strong liquidity and adequate capitalization, its debt structure requires further attention to enhance long-term financial stability